Financial work incentives in Britain: Comparisons over time and between family types - Stuart Adam; Mike Brewer; Andrew Shephard (Institute for Fiscal Studies (IFS), 2006)
This paper reviews various techniques for quantifying financial incentives to work, shows how financial work incentives have changed across the population since 1979, and estimates how much of these changes are due to changes in the tax and benefit system.
Keywords: 330